Analisis Faktor Kerusakan Vaksin Hewan Akibat Penyimpangan Suhu Dalam Proses Penanganan Aktivitas Inbound Pada PT. X - Zahra, Rizty Aulia; Maulana, Andy; Sholihah, Sita Aniisah (Jurnal Sistem Transportasi & Logistik, 2022)
Livestock vaccination is one strategy for improving meat feed quality and preventing bacterial contamination of animals. One of the most important aspects of the vaccination process, aside from administering the vaccine, is how it is handled. Temperature differences caused damage to animal vaccines at PT X. As the result, we will discuss factors that have the potential to damage animal vaccines due to changes in temperature in this study. The research applied fishbone diagram analysis tools and Failure Mode and Effect Analysis (FMEA) to determine which factors have an impact. The factors identified in the fishbone diagram have resulted, namely the limited space for handling animal vaccines, the lack of special training for staff in handling animal vaccines, staff negligence in handling animal vaccines, limited equipment in handling animal vaccines, the location of the animal vaccine storage warehouse is in a fairly hot area, and there is no special SOP for handling animal vaccines. By multiplying the Severity, Occurrence, and Detection values, the highest RPN value is 210 for the factor that there is no special SOP for handling animal vaccines.